Integrated singlecell and bulk RNA-seq analysis identifies a prognostic signature related to inflammation in colorectal cancer - Wen Yin; Yanting Ao; Qian Jia; Chao Zhang; Liping Yuan; Sha Liu; Wanmeng Xiao; Gang Luo; Xiaomin Shi; Chen Xin; Maolin Chen; Muhan Lü; et al. (Scientific Reports)
Abstract Inflammation can influence the development of CRC as well as immunotherapy and plays a key role in CRC. Therefore, this study aimed to investigate the potential of inflammation-related genes in CRC risk prediction. Inflammation gene models were constructed and validated by combining transcriptomic and single-cell data from TCGA and GEO databases, and the expression of inflammation-related genes was verified by RT-qPCR. We identified two molecular subtypes and three genetic subtypes, two risk subgroups according to median risk values, constructed a prognostic model including thirteen genes (TIMP1, GDF15, UCN, KRT4, POU4F1, NXPH1, SIX2, NPC1L1, KLK12, IGFL1, FOXD1, ASPG, and CYP4F8), and validated the performance of each aspect of the model in an external database. Patients in the high-risk group had worse survival with reduced immune cell infiltration and a greater tumor mutational load. The risk score correlated strongly with the immune checkpoints PD1, PDL1, PDL2, and CTLA4, and it is possible that high-risk patients are more sensitive to treatment involving immune checkpoints. In the single-cell data, GDF15 was most significantly expressed in cancer cell populations. Therefore, we further validated their expression in cells and tissues using qPCR. In summary, we developed a prognostic marker associated with inflammatory genes to provide new directions for subsequent studies and to help clinicians assess the prognosis of CRC patients as well as to develop personalized treatment strategies.